Pembelajaran Kooperatif Terpadu Cirkuit Training Meningkatkan Aktivitas, Keterampilan dan Hasil Belajar Permainan Bola Basket - Salmawati Salmawati (Peneliti.net, 2022)
This research is a classroom action research which consists of the pretest stage, the first cycle stage, the second cycle stage and the third cycle. Actions taken in each cycle include: (1) planning, (2) implementation, (3) observation, and (4) reflection. This research was conducted at SMP Negeri 4 Pati with the subjects of the study were students of class VIII-H totaling 36 students. The problems faced by teachers in the classroom are learning models that are less varied, lack of facilities, student activity is still low, students only do the movements they like. This classroom action research generally aims to improve learning outcomes and increase student activity, improve technical abilities. the basic techniques of students' basketball games are more evenly distributed, using learning time more effectively and efficiently. Data collection techniques include a test of the ability of the basic techniques of playing basketball, student activity observation sheets during learning, and teacher activity observation sheets, student response questionnaires before and after the implementation of learning. The data analysis technique used descriptive percentages to reveal the results of students' classical learning mastery. By using the Integrated Cooperative Learning Training circuit, the results of the first cycle show the success target of 70% of students achieving mastery learning. with the percentage of activity 76.66%. The results of the second cycle showed that 83.33% of students achieved mastery learning, with an active percentage of 88.88%. The results of Cycle III show the success target of 97.88% of students achieving mastery learning. Based on the percentage of classical completeness of student learning outcomes that exceeds 85%, this classroom action research has achieved indicators of success. The conclusion of this research is that Integrated Cooperative Learning Circuit Training can improve the ability of the basic techniques of basketball. The researcher's suggestions include: (1) integrated cooperative learning circuit training can be an alternative for Physical Education teachers to be applied to the basic technical material for big ball games (2) Physical Education teachers are expected to be able to innovate in using various models/methods and learning media.